Species diversity and distribution of the macro algae from Bach Long Vi Island, Vietnam - Nguyen, Quynh Nga; Nguyen, Thi Mai Anh; Vu, Manh Hung; Dam, Duc Tien (Vietnam Journal of Marine Science and Technology, 2024)
Research results on seaweed at four cross-sections of Bach Long Vi Island from 1994 onwards have shown that 129 species of macroalgae belong to 4 phyla. Among them, Cyanobacteria has ten species, accounting for 7.75% of the total number of species; Red seaweed (Rhodophyta) has 70 species (54.26%); Brown seaweed (Ochrophyta/Phaeophyta) has 27 species (20.93%), and Green seaweed (Chlorophyta) has 22 species (17.06%). They belong to 21 orders, 42 families, and 72 seaweed genera. The number of species in the studied transects ranges from 41 species (transect 4) to 99 species (transect 2) and averages 72.25 species/transect. The similarity coefficient of seaweed species at four surveyed transects ranged from 0.26 (between transects 1 and 4) to 0.74 (between transects 2 and 3) and averaged 0.48. Of the 129 known species, there were 44 species only distributed in the intertidal zone, accounting for 34.10% of the total number of species; 108 species are only distributed in the subtidal zone (83.72%) and 26 species are distributed in both intertidal and subtidal zones (20.15%); most species distributed from the low intertidal zone downward and are concentrated mainly in the low intertidal zone and the upper range of the subtidal zone. In terms of structure, the number of taxa ranges from 2 (Cyanophyta) to 12 (Rhodophyta). On average, 5.25 orders/phylum; of families from 4 (Cyanophyta, Ochrophyta) to 25 (Rhodophyta) and 10.5 families/order; of genera from 6 (Cyanophyta) to 42 (Rhodophyta) and 18; of species from 10 (Cyanophyta) to 70 (Rhodophyta) and 32.25. The average number of species/genera is quite large (32.25). However, some genera have only one species (Hydrocoryne, Asparagopsis, Parvocaulis, etc.), and some other genera have a more significant number of species (Dictyota: 10 species; Hypnea: 8 species; Peyssonnelia: 5 species, etc.). Among the families, some have only one genus (Peyssonneliaceae, Scytosiphonaceae, Codiaceae, etc.), but others have more genera (Dictyotaceae: 5, Boodleaceae: 4, Sargassaceae: 2, etc.). The total number of orders of the four phyla (Cyanophyta, Rhodophyta, Ochrophyta, and Chlorophyta) is 21. Of which, Cyanophyta has 2 orders, accounting for 9.5% of the total number of recorded orders: Rhodophyta (12 and 57.1%), Ochrophyta (4 and 19%), and Chlorophyta (3 and 14.4%).